2010
DOI: 10.14512/gaia.19.2.13
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does Journal Reputation Tell Us About the Academic Interest and Relevance of Economic Research? Empirical Analysis and Implications for Environmental Economic Research

Abstract: Unlike in other disciplines, research output in economics is commonly measured based on the disciplinary reputation of the journals in which an author has published. Here, I examine how much output measures based on journal reputation tell us about the academic interest and relevance of economic papers as measured by frequency of citation. Using data from the 2008 Handelsblatt ranking of economists in German speaking countries and interdisciplinary citation data from the Web of Science, I find that researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
3
Order By: Relevance
“…Bei jenem Ranking betrug die erklärte Varianz in analogen Analysen (analog zum 1., 3. und 4. Modell in Tabelle 1) 31, 8 und 3 Prozent (Schläpfer 2010). Die Punktwerte und Zitationshäufigkeiten der ersten 50 Forschenden im Handelsblatt ‐Ranking 2008 sind im aufgeführt 9…”
Section: Handelsblatt‐punktwerte Und Individuelle Zitierhäufigkeitunclassified
“…Bei jenem Ranking betrug die erklärte Varianz in analogen Analysen (analog zum 1., 3. und 4. Modell in Tabelle 1) 31, 8 und 3 Prozent (Schläpfer 2010). Die Punktwerte und Zitationshäufigkeiten der ersten 50 Forschenden im Handelsblatt ‐Ranking 2008 sind im aufgeführt 9…”
Section: Handelsblatt‐punktwerte Und Individuelle Zitierhäufigkeitunclassified
“…It has been suggested that peer assessment among scholars in a field provides an evaluation of perceptions of journal quality, journal use, and is an indicator of general value within a field. This technique of surveying scholars has been used in a number of other academic fields, including medicine (Yue, Wilson, & Boller, 2007), economics (Schläpfer, 2010), psychology (Catling, Mason, & Upton, 2009), sport management (Shilbury & Rentschler, 2007), and other areas (e.g., Extejt & Smith, 1990;Nederhof & Zwaan, 1991;Rousseau, 2008). Peer assessment provides another dimension of journal quality and can be performed within an academic specialty.…”
mentioning
confidence: 99%
“…This change is creating exceptional opportunity [60,64]. This reality is not addressed by traditional roadmapping techniques.…”
Section: Today's Pharmaceutical Innovations Are Creating New Businessmentioning
confidence: 99%
“…The new technologies used in pharmaceutical innovation development are disruptive in nature [64,65]. This has created great interest in the sector by firms and economic development professionals who are not currently involved in the pharmaceutical sector since they believe they can leapfrog existing and formerly essential infrastructure.…”
Section: Section 212 the Technology Basementioning
confidence: 99%
See 1 more Smart Citation